2018
DOI: 10.1002/ejp.1235
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural, morphological and electrophysiological assessment of the effects of type 2 diabetes mellitus on large and small nerve fibres in Zucker diabetic fatty, Zucker lean and Wistar rats

Abstract: ZDF rats presented a diabetic neuropathy involving large and small nerve fibres; additionally, ZL and WH rats also showed early small abnormalities in C-fibres, clearly detected by microneurography SIGNIFICANCE: This study provides a functional description of large and small nerve fibre function in a diabetic model that recapitulates many of the findings observed in patients suffering from type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…However, while previous studies in diabetic mice showed that heat hypoalgesia was accompanied by loss of plantar IENF and that NSI-189 restored both heat sensation and IENF density, the ZDF rats showed only a mild reduction in paw IENF density. A similar mild trend to decrease of paw IENF has been reported in ZDF rats [30], whereas others reported more marked deficits [26,31]. Survival and/or accelerated regrowth of IENF may reflect increased circulating insulin levels in the early stage, despite decreasing levels in the later stage, as sensory neuron energy balance, neurite outgrowth, and paw IENF density are modulated by insulin, independent of hyperglycemia [32][33][34][35].…”
Section: Discussionsupporting
confidence: 63%
“…However, while previous studies in diabetic mice showed that heat hypoalgesia was accompanied by loss of plantar IENF and that NSI-189 restored both heat sensation and IENF density, the ZDF rats showed only a mild reduction in paw IENF density. A similar mild trend to decrease of paw IENF has been reported in ZDF rats [30], whereas others reported more marked deficits [26,31]. Survival and/or accelerated regrowth of IENF may reflect increased circulating insulin levels in the early stage, despite decreasing levels in the later stage, as sensory neuron energy balance, neurite outgrowth, and paw IENF density are modulated by insulin, independent of hyperglycemia [32][33][34][35].…”
Section: Discussionsupporting
confidence: 63%
“…At present, the most objective, sensitive and reliable method to diagnose DNP is NET. NET electrophysiological examination is the gold standard for diagnosis, but the operation is complicated and costly (15)(16)(17)(18)(19), and if it is used as a routine examination item, patient compliance is poor. The screen efficiency of MNSI for DPN is better than that of the TCSS and the MNSI has the same diagnostic consistency with NET.…”
Section: Discussionmentioning
confidence: 99%
“…Axonal degeneration, with both primary and secondary demyelination, has been documented in nerve biopsies from both animal models and individuals with diabetic polyneuropathy [ 20 , 21 ]. In particular, impairment of the myelin sheath and Schwann cells has been shown.…”
Section: Pathophysiology Of Peripheral Neuropathy In Diabetesmentioning
confidence: 99%